Biological Effects of Exposure to a Radiofrequency Electromagnetic Field on the Placental Barrier in Pregnant Rats - Kim, Hye Sun (Bioelectromagnetics, 2021)
The placenta protects the fetus against excessive stress‐associated maternal cortisol during pregnancy. We studied whether exposure to radiofrequency electromagnetic field (RF‐EMF) radiation during pregnancy can cause changes in dams and their placentas. Pregnant Sprague–Dawley rats were divided into cage‐control, sham‐exposed, and RF‐exposed groups. They were exposed to RF‐EMF signals at a whole‐body specific absorption rate of 4 W/kg for 8 h/day from gestational Day 1 to 19. Levels of cortisol in the blood, adrenal gland, and placenta were measured by enzyme‐linked immunosorbent assay. Levels of adrenocorticotropic hormone and corticotropin‐releasing hormone were monitored in maternal blood. Expression levels of placental 11β‐hydroxysteroid dehydrogenase type 2 (11β‐HSD2) messenger RNA (mRNA) were measured by reverse transcription polymerase chain reaction. Morphological changes in the placenta were analyzed using hematoxylin and eosin staining. Fetal parts of the placenta were measured using Zen 2.3 blue edition software. Maternal cortisol in circulating blood (RF: 230 ± 24.6 ng/ml and Sham: 156 ± 8.3 ng/ml) and the adrenal gland (RF: 58.3 ± 4.5 ng/ml and Sham: 30 ± 3.8 ng/ml) was significantly increased in the RF‐exposed group (P < 0.05). Placental cortisol was stably maintained, and the level of placental 11β‐HSD2 mRNA expression was not changed in the RF‐exposed group. RF‐EMF exposure during pregnancy caused a significant elevation of cortisol levels in circulating blood; however, no changes in the placental barrier were observed in pregnant rats. Bioelectromagnetics. © 2021 Bioelectromagnetics Society